Pseudomonas syringae lytic transglycosylase HrpH interacts with host ubiquitin ligase ATL2 to modulate plant immunity - Jun-Zhou Li; Yi-Lin Gu; Wei Zhang; Shen Cong; Ruo-Na Wang; Yi-Nan Ma; Ya Jin; Hai-Lei Wei (Cell Reports)
Summary: Pseudomonas syringae deploys a type III secretion system (T3SS) to deliver effector proteins to facilitate infection of plant cells; however, little is known about the direct interactions between T3SS components and plants. Here, we show that the specialized lytic transglycosylase (SLT) domain of P. syringae pv. tomato (Pst) DC3000 T3SS component HrpH is necessary for effector translocation. HrpH and its SLT domain induce host cell death and suppress pattern-triggered immunity (PTI). Transgenic hrpH-Arabidopsis plants exhibit decreased PTI responses and enhanced susceptibility to Pst DC3000ΔhrcQ-U. HrpH suppresses salicylic acid (SA) signaling and interacts with the E3 ubiquitin ligase ATL2 via its SLT domain, independent of its catalytic glutamate. ATL2 silencing indicates that ATL2 is required for basal resistance to bacterial infection, HrpH-triggered cell death, and suppressing MAPK and SA signaling. Our findings highlight that beyond serving as a lytic transglycosylase for effector delivery, HrpH targets an E3 ligase to modulate plant immunity.